Mechanisms of Vascular Disease: A Reference Book for Vascular Specialists - Fitridge, Robert (University of Adelaide Press, 2011)
New updated edition first published with Cambridge University Press. This new edition includes 29 chapters on topics as diverse as pathophysiology of atherosclerosis, vascular haemodynamics, haemostasis, thrombophilia and post-amputation pain syndromes.